DNA methylation and hydroxymethylation have distinct genome-wide profiles related to axonal regeneration - Andy Madrid; Laura E. Borth; Kirk J. Hogan; Nithya Hariharan; Ligia A. Papale; Reid S. Alisch; Bermans J. Iskandar (Epigenetics, 2021)
Alterations in environmentally sensitive epigenetic mechanisms (e.g., DNA methylation) influence axonal regeneration in the spinal cord following sharp injury. Conventional DNA methylation detection methods using sodium bisulphite treatment do not distinguish between methylated and hydroxymethylated forms of cytosine, meaning that past studies report a composite of 5-methylcytosine (5mC) and 5-hydroxymethylcytosine (5hmC). To identify the distinct contributions of DNA methylation modifications to axonal regeneration, we collected spinal cord tissue after sharp injury from untreated adult F3 male rats with enhanced regeneration of injured spinal axons or controls, derived from folate- or water-treated F0 lineages, respectively. Genomic DNA was profiled for genome-wide 5hmC levels, revealing 658 differentially hydroxymethylated regions (DhMRs). Genomic profiling with whole genome bisulphite sequencing disclosed regeneration-related alterations in composite 5mC + 5hmC DNA methylation levels at 2,260 differentially methylated regions (DMRs). While pathway analyses revealed that differentially hydroxymethylated and methylated genes are linked to biologically relevant axon developmental pathways, only 22 genes harbour both DhMR and DMRs. Since these differential modifications were more than 60 kilobases on average away from each other, the large majority of differential hydroxymethylated and methylated regions are unique with distinct functions in the axonal regeneration phenotype. These data highlight the importance of distinguishing independent contributions of 5mC and 5hmC levels in the central nervous system, and denote discrete roles for DNA methylation modifications in spinal cord injury and regeneration in the context of transgenerational inheritance.